A Sequence-Based Predictor of Zika Virus Proteins Developed by Integration of PseAAC and Statistical Moments - Hussain, Waqar; Rasool, Nouman; Khan, Yaser D. (Combinatorial Chemistry & High Throughput Screening, 2020)
Background: ZIKV has been a well-known global threat, which hits almost all of the American countries and posed a serious threat to the entire globe in 2016. The first outbreak of ZIKV was reported in 2007 in the Pacific area, followed by another severe outbreak, which occurred in 2013/2014 and subsequently, ZIKV spread to all other Pacific islands. A broad spectrum of ZIKV associated neurological malformations in neonates and adults has driven this deadly virus into the limelight. Though tremendous efforts have been focused on understanding the molecular basis of ZIKV, the viral proteins of ZIKV have still not been studied extensively. Objectives: Herein, we report the first and the novel predictor for the identification of ZIKV proteins. Methods: We have employed Chou’s pseudo amino acid composition (PseAAC), statistical moments and various position-based features. Results: The predictor is validated through 10-fold cross-validation and Jackknife testing. In 10- fold cross-validation, 94.09% accuracy, 93.48% specificity, 94.20% sensitivity and 0.80 MCC were achieved while in Jackknife testing, 96.62% accuracy, 94.57% specificity, 97.00% sensitivity and 0.88 MCC were achieved. Conclusion: Thus, ZIKVPred-PseAAC can help in predicting the ZIKV proteins efficiently and accurately and can provide baseline data for the discovery of new drugs and biomarkers against ZIKV.
Keywords: prediction